Characterization and perspectives of pregnant women in a specialized prenatal service (Research, Society and Development, 2021)
Objective: to evaluate the outlook of pregnant women regarding pregnancy and specialized prenatal care in a city in the State of Minas Gerais, and to characterize the profile and expectations of the pregnant women assisted. Method: this is a descriptive, quali-quantitative study carried out in a specialized care service. The data were analyzed using descriptive statistics and Content Analysis (Bardin). Results: 41 pregnant women participated in the study, four (9.8%) of them were under 18 years, three (7.3%) of them were over 35 years, and 13 (31.7%) of them suffered from hypertension. The level of education was associated with participation in educational activities during prenatal care (c2(3)=6.258; p=0.100; Cramer's V=0.391) and the number of dependents and the month when the appointments started (ρ=0.356; p=0.031). The categories were the following: "Welcoming, Safety, and Security"; "Insecurity, Fear and Disappointment"; "Indifference" and "Expectations". Conclusion: the perception of pregnant women indicates gaps in care, as well as beliefs that can interfere with following up on pregnancy, meaning that effective welcoming and follow-up procedures are necessary.